Analisis Kepuasan Pelanggan Terhadap Fasilitas yang Disediakan oleh Pihak Transjakarta - Argirinata Pristanto; Omega Trifena Lauren; Danisa Aryani; Siti Sahara (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to analyze customer satisfaction with the facilities provided by Transjakarta to make it more effective and efficient. This research can also be used as a recommendation for the Transjakarta Party for future policies to improve the quality of Transjakarta Transportation. There is a method used in this study using a qualitative descriptive method which is divided into 2 types, namely Primary Data taken based on online surveys via GoogleForm and Secondary Data from additional information obtained from various books, journals or articles. After analyzing the opinions of the respondents, it can be concluded that the quality of the facilities provided by Transjakarta is quite good, but there are still several shelters with inadequate conditions, such as waiting areas. Therefore, the Provider must try to improve the quality of Transjakarta facilities, fully and evenly. So that users feel more secure and comfortable when using the Transjakarta mode of transportation.